Human to Human Transmission of Brucella Melitensis. (1995) - Vigeant, Patrice; Mendelson, Jack; Miller, Mark A
Abstract : Human brucellosis is acquired mainly through contact with infected animal tissues, ingestion of unpasteurized dairy products or infected aerosols. Person to person transmission is still considered uncertain. The case of a woman diagnosed with proven brucellosis after her husband suffered a relapse of bacteremia with Brucella melitensis biotype 3, which was originally acquired abroad by eating goat cheese, is described. It was postulated that person to person spread of brucellosis is a likely mode of transmission in this case.